Free cancer cells in gastric cancer – methods of detection, clinical and prognostic importance (meta-analysis) - Kołomańska, Magdalena; Głuszek, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2020)
Gastric cancer (GC) is one of the most common malignant cancers worldwide. Intraperitoneal dissemination is the typical mechanism of the formation of metastases in GC. The diagnosis of the presence of intraperitoneal free cancer cells (IFCCs) is treated equally to the M (metastasis) category according to the 8th edition of the TNM classification by the American Joint Committee on Cancer. IFCCs are cells which have detached from the primary tumour through exfoliation into the peritoneal cavity. The source of IFCCs may be iatrogenic due to improper surgical technique during resection of the tumour and may lead to intraperitoneal dissemination. Cytological examination of peritoneal lavage is considered as a gold standard in the confirmation of the presence of IFCCs; however, its sensitivity is very low. In order to increase the sensitivity and reliability of the examination, molecular biology techniques should be applied. In the case of detection of the presence of IFCCs in patients with GC, the patient should be qualified for chemotherapy, or possibly the use of hyperthermic intraperitoneal chemotherapy should be considered.